The Effect of The Situation Based Learning (SBL) Learning Model on Students' Mathematics Problem Solving Ability on The VIII Class SPLDV Materials at SMP Negeri 2 Bandar Tradaging - Ambarita, Ervita Murni; Sidabutar, Ropinus; Purba, Yoel Octobe (EduMatika: Jurnal MIPA, 2022)
The purpose of this study was to determine the effect of the use of the Situation Based Learning (SBL) learning model on the mathematical problem-solving ability of eighth grade students at SMP Negeri 2 Bandar Trade. The design of this study used a pretest-posttest Nonequivalent control group design. The population in this study were all class VIII students of SMP Negeri 2 Bandar Trade T.A 2022/2023, and the samples in this study were all students of class VIII-1 and class VIII-5 students of SMP Negeri 2 Bandar Trade T.A 2022/2023 totaling 60 students. The instruments used in this study are validity, reliability, level of difficulty of test items and distinguishing power of test items. The data obtained were then analyzed using data analysis techniques, the average value of the Situation Based Learning (SBL) learning model was 82.13 and the average mathematical problem-solving ability was 56.03. The results of hypothesis testing after obtained tcount = 4.97 and ttable = 1.671. It means that tcount is greater than ttable which indicates  is rejected. Based on the description, it is concluded that the use of Situation Based Learning (SBL) learning model has an influence on students' mathematical problem-solving abilities in SPLDV learning in class VIII of SMP Negeri 2 Bandar Trade